2011
DOI: 10.1038/cgt.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

MDA-7 results in downregulation of AKT concomitant with apoptosis and cell cycle arrest in breast cancer cells

Abstract: The melanoma differentiation-associated gene-7 (mda-7) is a known mediator of apoptosis in cancer cells but not in normal cells. We hypothesized that MDA-7 interferes with the prosurvival signaling pathways that are commonly altered in cancer cells to induce growth arrest and apoptosis. We also identified the cell signaling pathways that are antagonized by MDA-7 leading to apoptosis. Using an adenoviral expression system, mda-7 was introduced into the breast cancer cell lines SKBr3, MCF-7 and MDA-MB-468, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…Ad-mda-7 also showed slight decrease of Erk1/2 signaling and p53 expression levels, but their functional roles in cell death could be minimal. In contrast to the present study, previous studies demonstrated that Ad-mda-7 downregulated the Akt pathways [11][12][13] and enhanced the Erk1/2 pathways. 14 Nevertheless, Pataer et al 15 demonstrated that Ad-mda-7 upregulated phosphorylation of Akt but decreased total Akt levels as we observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Ad-mda-7 also showed slight decrease of Erk1/2 signaling and p53 expression levels, but their functional roles in cell death could be minimal. In contrast to the present study, previous studies demonstrated that Ad-mda-7 downregulated the Akt pathways [11][12][13] and enhanced the Erk1/2 pathways. 14 Nevertheless, Pataer et al 15 demonstrated that Ad-mda-7 upregulated phosphorylation of Akt but decreased total Akt levels as we observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Accumulative reports have shown that mda-7/IL-24 displays antitumor properties and inhibits cancer cell growth by inducing apoptosis and arresting cell cycle (Wang et al, 2007;Dent et al, 2010;Otkjaer et al, 2010;Wang et al, 2010;Valero et al, 2011). Previous studies have shown that LRP, MDR1, and MRP1 play important roles in tumor MDR.…”
Section: Discussionmentioning
confidence: 99%
“…It binds to cell surface receptors to induce transcriptional activation of signal transducers and activators of transcription 3-phosphorylation (Dumoutier et al, 2001;Zhang et al, 2011a). Previous studies have shown that mda-7/IL-24 inhibits cell growth and induces apoptosis in melanoma, lung cancer, and other tumor types (Dent et al, 2010;Otkjaer et al, 2010;Wang et al, 2010;Wei et al, 2010;Xiao et al, 2010;Bhutia et al, 2011;Valero et al, 2011). It has also been shown that mda-7/IL-24 could reduce angiogenesis in tumors (Wang et al, 2007;Chang et al, 2009), suggesting that it is a tumor suppressor gene.…”
mentioning
confidence: 99%
“…Loss of IL-24 expression has been found with the progression of several cancers, such as melanoma [7]. Although IL-24 exhibits interesting properties through various signaling pathways [8][9][10][11][12][13][14][15][16], the molecular mechanisms involved in the regulation of IL-24 expression and activation and its anticancer activity are not yet completely understood [17,18]. Recombinant IL-24 induces apoptosis in a broad range of human cancers including colorectal cancer (CRC), with no significant toxicity to normal cells [19].…”
Section: Introductionmentioning
confidence: 99%